Distribuição espacial de Enneothrips flavens, Moulton 1941 (Thysanoptera: Thripidae), na cultura do amendoim, utilizando geoestatística - Canuto, Débora Maria Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The peanut (Arachis hypogaea L.) is an oilseed crop of great importance in the national economy. However, this crop is attacked by thrips-of-silvering, Enneothrips flavens Moulton, during the cycle of the plant starting in the vegetative phase to the end of the reproductive phase, presenting critical period between 25 and 70 days after sowing, causing yield losses. Due to the damage they can cause, the Integrated Pest Management needs to be established, however, it is necessary to define the distribution and population dynamics of this insect in the environment. The objective of this study was to evaluate the spatial distribution of E. flavens using geostatistics, mapping spatial dependence and drawing krigging maps. The experiment was conducted at Fazenda de Ensino, Pesquisa e Extensão (FEPE), an experimental area of FCAV / UNESP, Jaboticabal, São Paulo, Brazil. The IAC Runner 886 peanut, grown in 1 ha (10,000 m2). Each plot had an area of 100 m2 (10 m x 10 m). The evaluations were performed in the field at the beginning of the vegetative phase at 19 days after sowing (DAS) to the end of the reproductive phase (101 DAS), totaling 12 surveys. In each plot were chosen five plants and the leaflet pointer was removed, counting the nymphs and adults of thrips-of-silvering. The use of geostatistics allowed to conclude that the pest showed aggregated distribution with spatial dependence in 7 of the 12 reviews, and the absence of spatial dependence indicated the presence of nugget effect on the other five. In the first evaluation, 19 days after sowing (DAS), it was identified that the pest infested the plant from the borders, indicating a possible relationship with the presence of alternative host plants in the area, because during the experiment existed soybean, corn and also tiguera peanut and weeds. The spherical model showed the best fit to the semivariogram, with a range varying from 36,14m to 60,61m (26 DAS to 48 DAS, respectively)

O amendoim (Arachis hypogaea L.) é uma oleaginosa de grande importância na economia nacional. No entanto, a cultura do amendoim é infestada pelo tripes-do-prateamento, Enneothrips flavens Moulton, durante o ciclo da planta com início na fase vegetativa até o fim da fase reprodutiva, apresentando período crítico dos 25 aos 70 dias após a semeadura, prejudicando sua produtividade. Devido aos danos que podem provocar, o Manejo Integrado da Praga precisa ser estabelecido, porém, é necessário definir a distribuição e flutuação populacional deste inseto no ambiente. Assim, o objetivo desse trabalho foi avaliar a distribuição espacial de E. flavens utilizando a geoestatística, visando mapear a dependência espacial e estabelecer mapas de interpolação por krigagem. O experimento foi conduzido na Fazenda de Ensino, Pesquisa e Extensão (FEPE) da Faculdade de Ciências Agrárias e Veterinárias (FCAV/UNESP), Campus Jaboticabal, São Paulo, Brasil. A variedade IAC Runner 886 foi cultivada em 1 hectare (10.000 m²), dividido em 100 parcelas de 100 m² cada (10 m x 10 m). As avaliações foram realizadas em campo no início da fase vegetativa aos 19 dias após a semeadura (DAS) até o fim da fase reprodutiva (101 DAS), totalizando 12 avaliações. Em cada parcela foram escolhidas 5 plantas ao caso e retirado o folíolo do ponteiro, realizando-se a contagem do número de ninfas e adultos do tripes-do-prateamento. A utilização da geoestatística permitiu concluir que a praga apresentou distribuição em reboleiras, de forma agregada com dependência espacial em 7 das 12 avaliações, e a ausência de dependência espacial indicou a presença do efeito pepita puro em 5 avaliações. Na primeira avaliação, aos 19 dias após semeadura (DAS), foi identificado que a praga infestou a planta a partir das bordaduras, indicando uma possível relação com a presença de plantas hospedeiras alternativas na área, pois durante o experimento ...
Keywords: Geologia - Métodos estatísticos; Amendoim - Doenças e pragas; Distribuição espacial da população; Inseto; Krigagem; Agricultural pests